Financial Administration Assistance In UMKM - Indrianasari , Neny Tri (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This Community Service Activity is expected to provide the following outcomes for partners understanding partners in financial management, implementation of financial reports in accordance with SAK EMKM. The implementation of this Community Service (PKM) activity is carried out using the lecture, tutorial and discussion methods. Based on the results of the implementation of activities that have been carried out, there are several things that can be concluded from this Community Service activity, namely a. The training that was carried out was able to increase the desire to learn more deeply about financial recording activities in particular and increase the ability to do business in general. b. Training participants are able to explain and understand basic accounting concepts, accounting cycles and accounting information systems, c. The training participants still have a lot to learn and practice in preparing financial reports based on SAK EMKM.